2021
DOI: 10.3389/fpsyg.2021.759616
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Impact of Mystery in Nature on Attention: An Oculometric Study

Abstract: Nature exposure can provide benefits on stress, health and cognitive performance. According to Attention Restoration Theory (ART), the positive impact of nature on cognition is mainly driven by fascination. Fascinating properties of nature such as water or a winding hiking trail may capture involuntary attention, allowing the directed form of attention to rest and to recover. This claim has been supported by studies relying on eye-tracking measures of attention deployment, comparing exposure to urban and natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…To date this is the first study to use pupillometry during a sustained attention task to test the immediate effects of viewing a nature image. The three other studies using pupillometry measured pupil diameter as participants viewed photos of different forms of nature, finding opposite effects ( Nordh et al, 2010 ; Martínez-Soto et al, 2019 ; Marois et al, 2021 ). Here, the participants showed physiological and behavioral evidence of fatigue during both the baseline and post-intervention SARTs, and reported feeling sleepier after completing both SARTs, but with no relief proffered by viewing the nature images for the 40 s period tested here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date this is the first study to use pupillometry during a sustained attention task to test the immediate effects of viewing a nature image. The three other studies using pupillometry measured pupil diameter as participants viewed photos of different forms of nature, finding opposite effects ( Nordh et al, 2010 ; Martínez-Soto et al, 2019 ; Marois et al, 2021 ). Here, the participants showed physiological and behavioral evidence of fatigue during both the baseline and post-intervention SARTs, and reported feeling sleepier after completing both SARTs, but with no relief proffered by viewing the nature images for the 40 s period tested here.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies to date have examined the associations between nature images and pupil diameter; participants viewed photographs rated either high or low in restorative value ( Nordh et al, 2010 ; Martínez-Soto et al, 2019 ; Marois et al, 2021 ). Nordh and colleagues noted that pupil size was smaller when participants viewed park photos they rated as more restorative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, images depicting settings high in mystery usually include soft fascination. Through a novel oculometric methodology to explore engagement with environments depicted in images, Marois et al [33] proposed that it is the voluntary engagement with mystery and soft-fascination components of nature that helps bring about restoration by reducing cognitive demand.…”
Section: The Role Of Mystery In Artmentioning
confidence: 99%
“…In order to quantify the connection between the biophilic design strategies and their impact on student and teacher performance, a thorough literature review identifying the relevant benefits of specific biophilic retrofit strategies to humans was completed and captured on the back of each strategy card. The studies found significant connections between biophilic design elements and human health and productivity outcomes, including anxiety and stress [24][25][26], attention [27][28][29][30], cognitive function [12,13,19,31], engagement (in class) [32], graduation rates [33], physical health [15,[34][35][36][37], standardized test scores [18,[38][39][40][41], systems thinking [42], teamwork [43], and thermal comfort [44].…”
Section: Introductionmentioning
confidence: 99%